(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Traditional medicine had become the oldest form of health care system in many countries of the world including Nigeria. The present study aimed at documenting ethnomedicinal plants for the treatment of snakebites in Katsina State, Nigeria. The target group of the population includes herbalists and snakebite victims; ethnobotanical information was obtained through an oral interview using a semi-structured questionnaire. A total of 300 respondents were interviewed in this study. The respondents exposed the use of 25 medicinal plants for the treatment of snakebites in the study area. The most commonly used plant family includes Adansonia digitata and Securidaca longepedunculata. Leaves were the most frequently reported plant parts by the respondents. The methods of preparation were usually by decoction or pounding the plants part into powder. Administration of the preparations is usually via topical (51%), topical/oral (26%) and oral (23%) routes. Preference ranking in this study revealed that Adansonia digitata and Securidaca longepedunculata were effective in neutralizing the venom of Bitis arientans this validates the claim of the traditional medical practictioners.